The future in their hands: Graduating student midwives' plans, job satisfaction and the desire to work in midwifery continuity of care. Issue 1 (February 2020) - Evans, Jo; Taylor, Jan; Browne, Jenny; Ferguson, Sally; Atchan, Marjorie; Maher, Penny; Homer, Caroline S.; Davis, Deborah
Abstract: Background: Midwife-led continuity of care models benefit women and the midwives who work in them. Australian graduate midwives are familiar with, and educated to provide, continuity of care to women although the opportunity to work exclusively in positions providing continuity of care on graduation is uncommon. Aim: To explore the immediate and aspirational employment plans and workforce choices, reasons for staying in midwifery and perceptions around factors likely to influence job satisfaction of midwives about to graduate from one Australian university during the years 2012–2016. Methods: This longitudinal study draws on survey responses from five cohorts of midwifery students in their final year of study. Findings: Ninety five out of 137 midwifery students responded to the survey. Almost nine out of ten respondents either aspired to work in a continuity of care model or recognised that they would gain job satisfaction by providing continuity of care to women. Factors leading to job satisfaction identified included making a difference to the women for whom they care, working in models of care which enabled them to provide women with 'the care I want to give', and having the ability to make autonomous midwifery decisions. Conclusion: Aligning early graduate work experiences with continuity of care models may have a positive impact on the confidence and professional development of graduate midwives, which in turn may lead to greater satisfaction and retention among a workforce already committed to supporting the maternity healthcare reform agenda.